Effect of moisture on hydrothermal modification of yam Dioscorea hispida Dennst starch - Jirarat Tattiyakul (2018)
Starch from Thai yam Dioscorea hispida Dennst; locally known as kloy kao niaw (KKN), was hydrothermally modified (HM) at moisture contents (MC) between 13 and 30 g water/100 g starch (wb) at 90°C for 10 h. All treatments caused a decrease in swelling power and amylose leaching, and an increase in gelatinization temperature of the starch indicating a strengthened network within the starch granule. However, when setting 7 g starch/100 g (wb) gelatinized starch dispersion to gel and subjecting the samples to dynamic rheological tests, only HM KKN starch modified at 13 g water/ 100 g starch (wb) gave starch gel with higher complex modulus (G*) when compared to native KKN starch gel over the test frequency range (0.001 to 30 Hz). The X-ray diffraction pattern revealed that KKN starch granule's crystalline structure changed from B to C-type when modified at 13 g water/100 g starch (wb) and stayed unchanged when modified at 18 to 30 g water/100 g starch (wb). © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.